Replication Data for "Taxing Informality: Compliance and Policy Preferences in Urban Zambia" - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
These files comprise data and do-files for reproducing results presented in the article "Taxing Informality: Compliance and Policy Preferences in Urban Zambia" (Resnick, 2020). The dataset "Zambia_informal_taxation.dta" is constructed from the Lusaka Market Study on Taxation and Service Delivery, 2020. The sampling procedure employed is described in section 4 of the article.